Leerlingprestaties in de exacte vakken in groep 6 van het basisonderwijs Resultaten TIMSS-2019 - Meelissen, Martina (Universiteit Twente, 2020)
In the spring of 2019, 3355 Dutch students in group 6 of primary education from 112 schools participated in eTIMSS-2019. TIMSS stands for Trends in International Mathematics and Science Study and measures worldwide developments in knowledge and skills in science and in attitudes of students who have completed four or eight years of formal education. The 'e' of eTIMSS refers to the digital administration of the test. In the Netherlands, group 6 students took the 2019 TIMSS test on a tablet. The students have been tested in mathematics and science (biology, physics and chemistry and physical geography). The present report reports on the outcomes of TIMSS-2019 in the Netherlands. The remainder of this chapter describes the structure of TIMSS-2019.